In situ remineralization of white-spot enamel lesions by 500 and 1,100 ppm F dentifrices - Mensinkai, Poornima K.; Ccahuana-Vasquez, Renzo A.; Chedjieu, Irene; Amaechi, Bennett T.; Mackey, Allen C.; Walker, Trenton J.; Blanken, Douglas D.; Karlinsey, Robert L. (Clinical oral investigations, 2012)
The aim of this study was to evaluate the remineralization potential of three silica-containing NaF dentifrice systems in an intraoral model. Subjects ( N = 30) in this randomized, three-phase, 28-day, crossover study served as their own control. Each participant wore a customized orthodontic appliance attached to a mandibular molar and contained one tooth block with caries-like lesion. For each phase, participants engaged in twice-daily brushing for 2 min with one of the following dentifrices: 500 ppm F, 500 ppm F plus functionalized β-tricalcium phosphate (fTCP), and a clinically proven 1,100 ppm F. After each phase, appliances were removed, and specimens were analyzed using surface microhardness (SMH), transverse microradiography (TMR), and cross-sectional microhardness (CSMH). Statistically significant ( p < 0.05) remineralization of white-spot lesions relative to baseline occurred for each dentifrice as determined with SMH and TMR. No significant differences ( p > 0.05) in SMH were found among the three groups, but trending revealed the 500 ppm F plus fTCP produced 26% and 27% greater SMH recovery relative to 500 and 1,100 ppm F, respectively. Similarly, no significant differences ( p > 0.05) in TMR were found among the groups. However, the 500 ppm F plus fTCP dentifrice produced 10% and 38% greater mineral recovery relative to 500 and 1,100 ppm F, respectively, while reducing the lesion depth 30% and 52%, respectively. Significant differences ( p < 0.05) in CSMH existed among the three dentifice groups at different enamel depths, but statistical differences ( p < 0.05) in relative lesion size were only found between 500 ppm F plus fTCP and 500 ppm F. The combination of fTCP and fluoride in a single-compartment, water-based dentifrice can cooperate with fluoride to produce significant remineralization. These results suggest that the combination of 500 ppm F with fTCP may provide comparable anticaries benefits relative to a 1,100 ppm F dentifrice.